A Randomized Trial of Brief Interventions for Problem and Pathological Gamblers - Petry, Nancy M. (2008)
Limited research exists regarding methods for reducing problem gambling. Problem gamblers (N=180) were randomly assigned to: assessment only control, 10 minutes of Brief Advice, 1 session of motivational enhancement therapy (MET), or 1 session of MET plus 3 sessions of cognitive-behavioral therapy (CBT). Gambling was assessed at baseline, 6 weeks later, and a 9-month follow-up. Relative to assessment only, Brief Advice was the only condition that significantly decreased gambling between baseline and week 6, and it was associated with clinically significant reductions in gambling at month 9. Between week 6 and month 9, MET+CBT evidenced significantly reduced gambling on one index compared to the control condition. These results suggest the efficacy of a very brief intervention for reducing gambling among problem and pathological gamblers not actively seeking gambling treatment.